Antioxidant and antimicrobial effects of edible coating based on chitosan and bamboo vinegar in ready to cook pork chops. (July 2018) - Zhang, Huiyun; He, Peng; Kang, Huaibin; Li, Xinling
Abstract: Edible coating solutions, containing chitosan (CH) and bamboo vinegar (BV), were developed to investigate the effect of CH-BV coating solutions on quality and shelf life of ready to cook (RTC) pork chops stored at 4 ± 1 °C for 12 days. The antioxidant effects against lipid oxidation and antimicrobial activity against total viable counts (TVC), lactic acid bacteria (LAB), Enterobacteriaceae, and Pseudomonus spp. were analyzed. At the same time, Changes in color parameters and sensory attributes of all RTC samples were evaluated. Results showed that CH-BV coating treatments tended to retard lipid oxidation by inhibited the increases in TBARS values. CH coating treatments enhanced L* and maintained a* values almost stable during storage. Compared to the control sample, CH and CH-BV coating treatments maintained the initial color values of samples for a longer period according to DE* values. Based primarily on microbiological and sensory data, CH and CH-BV coating treatments improved shelf-life by ca. 3 and 6 days, respectively. Therefore, bamboo vinegar-based edible coating treatment could be applied to RTC meat products to improve product's shelf life and food safety. Highlights: Bamboo vinegar was blended with chitosan to develop an active edible coating. Antioxidant and antimicrobial effect of active coating on RTC pork chops was observed. Active coating had no adverse effect on the sensory attributes of RTC pork chops. Shelf life of RTC pork chops increases 6 days with the active coating treatment.